Landslide hazard assessment of the fault zone considering the fault effect: a case study of the Lixian–Luojiabu fault zone in Gansu Province (China) - Feng, Wei; Tang, Yaming; Ma, Hongli; Hong, Bo (Frontiers in Earth Science, 2024)
The earthquake landslide hazard assessment method is mainly based on the traditional Newmark model. However, when landslide hazard assessment is carried out along the fault zone, the calculated results are often different from the actual situation because the influence of fault effect is not fully considered. Therefore, how to construct a landslide hazard assessment model suitable for the fault zone is a technical problem to be solved by researchers. Taking the Lixian-Luojiabu fault zone in Gansu Province in China as the study area, this paper put forward the concept of fault effect correction coefficient exploringly, systematically studied the relative distance relationship between landslide and fault zone, and the relative position relationship between landslide and upper and lower sides of fault zone. The value table of fault effect correction coefficient along the Lixian-Luojiabu fault zone was established, and the corresponding distribution map of fault effect correction coefficient was drawn. Based on this, an improved Newmark model for landslide hazard assessment along fault zone was constructed. On the basis of systematic analysis of slope and engineering geological rock group in the study area, traditional Newmark model and improved Newmark model considering fault effects were used respectively to carry out earthquake landslide hazard assessment under the condition of 10% exceeding probability in 50 years, and ROC curve method and Kappa coefficient method were used to compare and analyze the evaluation results. The results showed that the AUC value and Kappa coefficient of the danger area obtained by the improved model with Newmark were 0.841 and 0.822, which were significantly higher than the calculated values of traditional model with Newmark, indicating that the model had a good improvement effect. The Newmark improved model considering fault effect fully considered the influence of distance from fault zone and fault upper and lower sides effect, and the research results can provide a new reference for landslide hazard assessment along fault zone.